MODEL LEMBAGA KEUANGAN MIKRO POLA GRAMEEN BANK UNTUK PENGUATAN KLASTER (di Kab. Brebes dan Kota Surakarta) - Sriyanto Sriyanto; Wiwin Widiastuti (JURNAL LITBANG PROVINSI JAWA TENGAH, 2013)
Strengthening of the cluster is affected by the factors of production, including capital. The goal is : to identify the structure of the chain of activites, capital reqirements, financial institutions and role models pattern of Microfinance Institution Grameen for strengthening clusters. Research sites in coastal areas (clusters of seaweed in Brebes) and the highlands (batik cluster in Surakarta). The results, that : Characteristics of clusters varies influent by local socio cultural factors. Structure activity of clusters is different. Capital requirements are relatively small, less than Rp.5 million as much as 80,00 %. Non-formal financial institutions nearby PNPM Mandiri. Influencing factors : management, solidarity, and loyalty members and mutual trust (mutual trust in group). Model financial institutions the right pattern of Grameen Bank is a form of cooperative (owned and affiliated members of the cluster). The working principle of Grameen Bank modified into AD/ART of cooperative. Cluster development is inseparable from the aspect chain upstream (input) – processing (industrial) and downstream (marketing) and involving cross-sector and private. Agricultural institutions preparing raw materials, facilitating the establishment of cooperative and capital stimulants. The Planning Board Institution designing the strengthening of institutions, management and technical skills of entrepreneurship.